V chem osnovnaya prichina neudachnogo vystupleniya rossiiskikh sportsmenov na olimpiade v Sidnee v tsiklicheskikh vidakh sporta, svyazannykh s proyavleniem vynoslivosti - Jakimov, A. M. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
It is analyzed why the Russian athletes in endurance sports showed such an unsufficient performance at the Olympiad in Sydney 2000 where they won only one gold medal (the plan had been 10!).